Applied approach to privacy and security for the internet of things - Chatterjee, Parag, 1992-; Benoist, Emmanuel, 1972-; Nath, Asoke, 1953- (Advances in information security, privacy, and ethics (AISPE) book series., 2020)
"This book examines the conceptual aspects of security and privacy in IoT. It also explores the application of IoT systems in smart transports, smart cities, and smart healthcare"--